Localising urban sustainability indicators: The CEDEUS indicator set, and lessons from an expert-driven process. (June 2020) - Steiniger, Stefan; Wagemann, Elizabeth; de la Barrera, Francisco; Molinos-Senante, María; Villegas, Rodrigo; de la Fuente, Helen; Vives, Alejandra; Arce, Guillermo; Herrera, Juan-Carlos; Carrasco, Juan-Antonio; Pastén, Pablo A.; Muñoz, Juan-Carlos; et al.
Abstract: The development and application of urban sustainability indicators has gained momentum in recent years, especially since the generation of specific urban indicators for the Agenda 2030. Urban sustainability is a broad concept involving many dimensions, therefore the generation of a short, but comprehensive list of indicators is a significant challenge. In this paper, we present a set of 29 indicators designed to characterise urban sustainability in Chile, which we also expect to be relevant to other cities, particularly in the Global South where issues of poverty and inequality are prevalent. We first outline the process of selecting the indicators through expert consultation. Then we present selected indicators, and the variables used to measure them. Subsequently the set is applied to six Chilean cities that are diverse in terms of population, socio-economic conditions and geography. We show that some indicators highlight negative nationwide trends that are common to the cities, while other indicators reveal notable differences that can be traced back to their local contexts. The CEDEUS indicators provide a complement to the UN's Sustainable Development Goals (SDGs) for cities; therefore, a comparison is made with the SDGs. The indicator development process is critically examined and policy recommendations are given. Highlights: An expert-based process is presented to identify local urban sustainability indicators. 5 sustainability categories with 29 indicators were identified. A measurement variable is presented for each indicator. Indicator variables are used to characterise 6 cities in Chile of different size, economic and geographical context. Relationship between the indicator set and the 2030 Agenda's Sustainable Development Goals are evaluated.